Investment appraisal : - Lumby, Stephen (Van Nostrand Reinhold, 1985)
This expanded edition now includes all the material required for a course in financial management. An expansion of the range of topics covered makes it possible to use this book as the core text for a wider variety of courses. Changes to this edition have been based on the feedback from adopting lecturers. Answers to all end-of-chapter questions in an accompanying teacher's manual make this book a useful teaching tool.